Burkitt lymphoma presenting as intussusception in an adult: A rare entity - Pandya, Jayashri Sanjay; Modi, Jaini Bhavesh; Waghmare, Sudatta (Indian Journal of Case Reports, 2018)
Intussusception is uncommon among adults. Burkitt lymphoma (BL) of the intestine is a rare entity. It is more common in lymphoid organs, tonsils, and in the midline. Here, we report the case of a 28-year-old man who presented as an ileocolic intussusception. A resection of the specimen was done which was suggestive of BL. Adjuvant treatment in the form of chemotherapy regimen R-EPOCH comprising rituximab, vincristine, cyclophosphamide, doxorubicin, and oral prednisolone was given.